Improving Knowledge and Practical Skills for Better Farm Management in Body Condition Score Assessment in Pombulaa Jaya Village, Konda District - Harapin Hafid; Zahra Jinan Fadilla (Journal of Saintech Transfer, 2026)
This study aims to improve the knowledge and skills of prospective cattle fatteners in Pombulaa Jaya Village, Konda District in assessing Body Condition Score (BCS). BCS is an important indicator for assessing body fat reserves, which influences productivity, reproductive efficiency, and sustainability of livestock farming. The program involved 15 participants. The intervention consisted of an interactive educational session, demonstration, and supervised hands-on field practice using visual observation and palpation techniques. Program effectiveness was evaluated using pre-test and post-test questionnaires and direct observation of participants' practical skills. A paired-samples t-test was used to compare participants' knowledge scores before and after the training. The results showed a significant improvement in participants' knowledge, with the mean score increasing from 57.67 ± 7.04 before training to 96.67 ± 3.62 after training (p < 0.001). Participants also demonstrated improved competency in identifying BCS categories during the practical assessment. These findings indicate that combining theoretical instruction with demonstration and supervised hands-on practice effectively enhances participants' knowledge and practical competency in BCS assessment. Improved competency in BCS assessment may support better decision-making in cattle nutrition, health monitoring, and reproductive management. Further studies are needed to evaluate the long-term impact of this educational program on livestock productivity and farm performance.